2012
DOI: 10.1128/aac.05946-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Genetic Characterization of the Tap Efflux Pump in Mycobacterium bovis BCG

Abstract: Efflux pumps extrude a wide variety of chemically unrelated compounds conferring multidrug resistance and participating in numerous physiological processes. Mycobacterium tuberculosis possesses many efflux pumps, and their roles in drug resistance and physiology are actively investigated. In this work we found that tap mutant cells showed changes in morphology and a progressive loss of viability upon subcultivation in liquid medium. Transcriptome analysis in Mycobacterium bovis BCG revealed that disruption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 65 publications
5
60
1
Order By: Relevance
“…To support the relevance of our transcriptomics approach to study M. tuberculosis responses to the lysosomal environment, we selected one gene candidate, Rv1258c, which was found highly expressed under iLivE conditions and functionally relevant as a membrane Tap-like efflux pump (84)(85)(86). A previous study reported that M. tuberculosis transposon mutants of Rv1258c displayed reduced viability at 96 h postmacrophage infection (71).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the relevance of our transcriptomics approach to study M. tuberculosis responses to the lysosomal environment, we selected one gene candidate, Rv1258c, which was found highly expressed under iLivE conditions and functionally relevant as a membrane Tap-like efflux pump (84)(85)(86). A previous study reported that M. tuberculosis transposon mutants of Rv1258c displayed reduced viability at 96 h postmacrophage infection (71).…”
Section: Resultsmentioning
confidence: 99%
“…Our results support a role for Rv1258c in M. tuberculosis survival during exposure to the lysosomal content. Previous literature proposed that the Tap efflux pump activity helps mycobacteria cope with the hostile environment by pumping out hostderived antimicrobial molecules (84)(85)(86). To test whether the Tap efflux pump activity is involved in the M. tuberculosis response to SF killing, the Ox-Rv1258c strain was incubated with SF in the presence of the proton motive force inhibitor CCCP.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, whiB7 is highly up-regulated in macrophages (11) and in the lungs of infected animals (12). WhiB7 activates expression of its own regulon that includes resistance genes involved in antibiotic efflux (tap, Rv1258c) (13), ribosome modification (erm, Rv1988) (14,15), modulation of the host immune responses (eis, Rv2416c, and erm) (16,17), and mycobacterial survival within macrophages (eis) (7).…”
mentioning
confidence: 99%
“…In addition, the nucleotide sequence of the Rv1258c gene has been investigated as a potential STR-resistance determinant, since this gene encodes the drug efflux pump Tap in M. tuberculosis, which transports STR and other antibiotics (9)(10)(11). A nucleotide insertion in the coding sequence of the Rv1258c gene has been identified, which does not seem to be associated with resistance to this drug.…”
mentioning
confidence: 99%